COPPER AND COPPER-CONTAINING PESTICIDES: METABOLISM, TOXICITY AND OXIDATIVE STRESS - Viktor Husak (Vasyl Stefanyk Precarpathian National University, 2015)
The purpose of this paper is to provide a brief review of the current knowledge regarding metabolism and toxicity of copper and copper-based pesticides in living organisms. Copper is an essential trace element in all living organisms (bacteria, fungi, plants, and animals), because it participates in different metabolic processes and maintain functions of organisms. The transport and metabolism of copper in living organisms is currently the subject of many studies. Copper is absorbed, transported, distributed, stored, and excreted in the body via the complex of homeostatic processes, which provide organisms with a needed constant level of this micronutrient and avoid excessive amounts. Many aspects of copper homeostasis were studied at the molecular level. Copper based-pesticides, in particularly fungicides, bacteriocides and herbicides, are widely used in agricultural practice throughout the world. Copper is an integral part of antioxidant enzymes, particularly copper-zinc superoxide dismutase (Cu,Zn-SOD), and plays prominent roles in iron homeostasis. On the other hand, excess of copper in organism has deleterious effect, because it stimulates free radical production in the cell, induces lipid peroxidation, and disturbs the total antioxidant capacity of the body. The mechanisms of copper toxicity are discussed in this review also.